Review artikel: metode analisis dalam pengujian kandungan pewarna merah K10 (Rhodamin B) pada kosmetik - Vista Kamilania; Patihul Husni (Journal of Pharmaceutical and Sciences, 2023)
Cosmetics are products used to improve the appearance of the outer body. Cosmetics are inseparable from dyes. One dye that is often misused in cosmetic products is Rhodamine B. Rhodamine B can cause liver damage and irritation of the respiratory tract and is carcinogenic. This review article aims to provide information on the use of analytical techniques to identify cosmetic products containing rhodamine B. The method used is a literature review by searching research journals with a period of 2013-2023 on Science Direct and Google Scholar using the keywords "identification of k10 red dye in cosmetics", "rhodamine B analysis in cosmetics," and "k10 red dye analysis method in cosmetics". Based on the literature review that has been carried out, identifying the content of rhodamine B dye can be done with various analysis techniques including Thin Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC), UV Vis Spectrophotometry, Ultra Performance Liquid Chromatography Tandem Mass Spectrometric (UPLC-MS), and rapid test kit. Qualitative analysis of rhodamine B content in cosmetics can be done with KLT and a rapid test kit. Quantitative analysis can be done using UV Vis, KCKT, and UPLC MS spectrophotometry methods.